A hybrid drive parallel arm for heavy material handling. - Arai, T. (IEEE Robotics and automation magazine)
This article discusses a hybrid drive parallel arm driven by cables and cylinders in order to design a compact handling arm, thus enlarging its workspace. Our major objective is to develop a dexterous arm capable of controlling six-degree-of-freedom (DOF) motion of heavy materials. The article includes a basic concept of parallel mechanisms with hybrid actuation, comparisons and evaluations of some types of hybrid mechanisms based on its kinematics and statics, and finally introduces a designed prototype arm